Accurate O2 delivery enabled benzene biodegradation through aerobic activation followed by denitrification‐coupled mineralization. Issue 8 (7th May 2018) - Liu, Zhuolin; Zhou, Chen; Ontiveros‐Valencia, Aura; Luo, Yi‐Hao; Long, Min; Xu, Hua; Rittmann, Bruce E.
Abstract: Although benzene can be biodegraded when dissolved oxygen is sufficient, delivering oxygen is energy intensive and can lead to air stripping the benzene. Anaerobes can biodegrade benzene by using electron acceptors other than O2, and this may reduce costs and exposure risks; the drawback is a remarkably slower growth rate. We evaluated a two‐step strategy that involved O2 ‐dependent benzene activation and cleavage followed by intermediate oxidation coupled to NO3 − respiration. We employed a membrane biofilm reactor (MBfR) featuring nonporous hollow fibers as the means to deliver O2 directly to a biofilm at an accurately controlled rate. Benzene was mineralized aerobically when the O2 ‐supply rate was more than sufficient for mineralization. As the O2 ‐supply capacity was systematically lowered, O2 respiration was gradually replaced by NO3 − respiration. When the maximum O2 ‐supply capacity was only 20% of the demand for benzene mineralization, O2 was used almost exclusively for benzene activation and cleavage, while respiration was almost only by denitrification. Analyses of microbial community structure and predicted metagenomic function reveal that Burkholderiales was dominant and probably utilized monooxygenase activation, with subsequent mineralization coupled to denitrification; strict anaerobes capable of carboxylative activation were not detected. These results open the door for a promising treatment strategy that simultaneously ameliorates technical and economic challenges of aeration and slow kinetics of anaerobic activation of aromatics. Abstract : Nonporous hollow fibers enabled accurate O2 delivery on demands. When the maximum O2 ‐supply capacity was only 20% of the demand for benzene mineralization, O2 was used almost exclusively for benzene activation and cleavage, while respiration was almost only by denitrification. It opens the door for a promising treatment strategy that simultaneously ameliorates technical and economic challenges of aeration and slow kinetics of anaerobic activation of aromatics.